Imaging real-space flat band localization in kagome magnet FeSn - Daniel Multer; Jia-Xin Yin; Md. Shafayat Hossain; Xian Yang; Brian C. Sales; Hu Miao; William R. Meier; Yu-Xiao Jiang; Yaofeng Xie; Pengcheng Dai; Jianpeng Liu; Hanbin Deng; et al. (Communications Materials, 2023)
Direct imaging and tuning of flat band localization in kagome materials remains a challenge. Here, scanning tunneling microscopy and photoemission spectroscopy are used to study FeSn, revealing real-space localization and magnetic tuning of the flat band state within the Fe3Sn kagome lattice layer.